2019
DOI: 10.1080/15476286.2019.1667741
|View full text |Cite
|
Sign up to set email alerts
|

Systematic assessment of commercially available low-input miRNA library preparation kits

Abstract: High-throughput sequencing is increasingly favoured to assay the presence and abundance of microRNAs (miRNAs) in biological samples, even from low RNA amounts, and a number of commercial vendors now offer kits that allow miRNA sequencing from sub-nanogram (ng) inputs. Although biases introduced during library preparation have been documented, the relative performance of current reagent kits has not been investigated in detail. Here, six commercial kits capable of handling <100ng total RNA input were used for l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 53 publications
3
50
2
Order By: Relevance
“…2). In agreement with other recent studies 3,25,26 , we found a strong correlation between UMI counts and raw read counts, suggesting relatively little PCR bias exists within our samples. This suggests one might dispense with UMIs altogether in smRNA sequencing, though for low concentration samples that require more extensive amplification, we have found UMIs are helpful to maintain information of relative miRNA expression (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…2). In agreement with other recent studies 3,25,26 , we found a strong correlation between UMI counts and raw read counts, suggesting relatively little PCR bias exists within our samples. This suggests one might dispense with UMIs altogether in smRNA sequencing, though for low concentration samples that require more extensive amplification, we have found UMIs are helpful to maintain information of relative miRNA expression (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…1A ). To aid comparison, we present here the results of all eight kits, with our previous results [ 8 ] displayed in faded colours in the figures. Following library preparation, the NEBNext and NEXTflex libraries were sequenced together (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Following library preparation, the NEBNext and NEXTflex libraries were sequenced together (i.e. on the same sequencing flow cell) with the libraries from the other six library preparation kits [ 8 ]. Previously-published samples were not re-sequenced: the new data presented here was generated at the same time as those presented earlier, thus partial figures reproduced from the earlier study to aid comparison did not entail re-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations